Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 30, 1929 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1929)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 30, 1929. In the first month of 1864, interest in presidential politics was lively in spite of the war. Renomination of Lincoln, of course, was considered. Others were ambitious, including some in his cabinet. Hawley had considerable admiration for Lincoln but felt that he had weaknesses and that he was sometimes influenced against his own common sense.
1 electronic record. Scanned newspaper article. 1 image scans. 894 KB (915,577 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 22.2 MB (23,300,743 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers